Performance Efficiency Measurement in Managing Elementary Schools by Using a Robust Data Envelopment Analysis - Rokhmaniyah; Umi Mahmudah; Siti Fatimah (Jurnal Pendidikan Indonesia, 2023)
Efficiency is one of the determinants of the quality of education in schools. This study aimed to measure the performance of Indonesian provinces in managing elementary schools by using Data Envelopment Analysis (DEA). This research is evaluation-research using a quantitative approach. As many as 34 provinces in Indonesia were defined as DMUs by using six input variables, namely the number of schools, the number of teachers, the number of teachers certified more than the degree of bachelor, the number of students, the number of classes, and the number of libraries. Meanwhile, there were three output variables, namely the number of graduates, the number of schools that were A-accredited, and the average national exam. The robust data envelopment analysis (RDEA) applied the number of replications B=100, 500, and 1000. The results indicated that RDEA provided better accuracy and preciseness. Overall, all 34 provinces in Indonesia were found to have good performances in managing elementary schools where their efficiency scores were above 90% for both the traditional DEA and RDEA approaches. The implications of this research can be used as a study for stakeholders in making policies to improve the quality of education.